Plant Nutrition Monitoring System for Water Spinach Based on Internet of Things - Alviana, Sopian; Dwi Nugraha, Rizki; Kurniawan, Bobi (Universitas Komputer Indonesia, 2024)
The concept of plants using a hydroponic system has been widely used. Currently, the weakness in the management of the hydroponic system is the difficulty in managing the nutritional needs of plants. Nutrition is the main requirement for plants with the concept of a hydroponic system. In this research, a system will be proposed that can monitor the nutritional needs of hydroponic plants with a concentration of water spinach plants. The use of internet of things technology is proposed to be able to monitor in real time. With the existence of a monitoring system in real time, it can make it easier to monitor and control the nutritional needs of kangkong plants using a smartphone.